Strategy and Role of Public Sector Leadership in Managing Local Government Collaboration - Muammar Amar Alkadafi; Susanti Susanti (Department of Public Administration, 2023)
Local government organizations experience various obstacles and limitations in implementing the main objective of the decentralization policy, namely administrative decentralization. This goal is essentially the leader of local government organizations carrying out a mission to provide excellent service to the community. Literature studies from various research results from public administration experts reveal that government collaboration is a modern government strategy today to answer and at the same time become a solution to various problems of administering government, especially for local governments. This paper was prepared using the “literature review” method which focuses on revealing how the leadership of regional heads successfully manages government collaboration and how the strategies and leadership roles of public sector organizations in local government manage government collaboration that have an impact on improving service performance to the community. The results of the study recommend that local government leadership requires a transformative leadership strategy, internal and external multi-stakeholder program innovation strategies to carry out positive change agendas. In addition, more specifically, the leaders of government organizations can apply the strategy of “knowledge sharing, designing innovation solutions, Forging consequent change”, and leadership roles as integrators, facilitators, participatory and adaptive.